The Marketing Mix Strategy and Its Impact on Sales Volume Improvement at PT. Hadji Kalla in Ajatappareng - Musakkir , Musakkir; Damirah, Damirah; Muliati, Muliati; Aminah, St.; Semaun, Syahriyah (Economos : Jurnal Ekonomi dan Bisnis, 2024)
This study discusses the Marketing Mix Strategy and Its Impact on Sales Volume Improvement at PT. Hadji Kalla in Ajatappareng. The objective of this research is to understand the process of marketing strategy in increasing sales volume and the implementation of the Marketing Mix strategy to create customer satisfaction at PT. Hadji Kalla in Ajatappareng. The research method used is descriptive qualitative. This study is a field research. The data sources include primary data from direct interviews with the branch manager and marketing staff of PT. Hadji Kalla in Ajatappareng, and secondary data from books, journals, and related articles. Data analysis techniques involve SWOT analysis and data collection, data reduction, data presentation, and conclusion drawing. Data validity is tested using credibility and dependability tests. The marketing strategy of PT. Hadji Kalla in Ajatappareng has successfully increased sales by expanding target markets, improving product quality, offering attractive promotions, ensuring customer satisfaction, retaining and nurturing loyal customers, optimizing media use, providing product guarantees, proving with testimonials and reviews, employing bundling strategies, and conducting appropriate evaluations. To enhance customer satisfaction, PT. Hadji Kalla in Ajatappareng uses the 7P Marketing Mix strategy, which consists of product, price, place, promotion, people, process, and physical evidence. These seven elements have been well implemented and executed at PT. Hadji Kalla. The company offers a comprehensive product line and standard quality, affordable prices even with frequent customer discount requests, a strategic, comfortable, and clean location, affordable and effective promotions, friendly staff, adequate physical evidence, and a simple and practical delivery process.